Fault detection and isolation using neural networks in structural dynamic systems - Pandian Thirupura Sundari (2008)
In general, there is a possibility of degradation in stiffness due to environmental loadings such as earthquakes, for multi-storey steel frame structures, which are designed with enough stiffness and strength. Study on the identification of failure of such systems and taking corrective actions will go a long way in improving the safety of the systems. In this dissertation, the above structural dynamic system represented by a spring mass damper system (two masses) is considered here for the ease and understanding of solving this problem.